Involvement of pituitary gonadotropins, gonadal steroids and breeding season in sex change of protogynous dusky grouper, Epinephelus marginatus (Teleostei: Serranidae), induced by a non-steroidal aromatase inhibitor - Garcia, Carlos Eduardo de O.; Araújo, Bruno C.; Mello, Paulo H.; Narcizo, Amanda de M.; Rodrigues-Filho, Jandyr A. [UNESP]; Medrado, Andreone T.; Zampieri, Ricardo A.; Floeter-Winter, Lucile M.; Moreira, Renata Guimarães (Elsevier, 2013)
Two experiments were performed using the aromatase inhibitor (AI) letrozole (100mg/kg) to promote sex change, from female-to-male, in protogynous dusky grouper. One experiment was performed during the breeding season (spring) and the other at the end of the breeding season (summer). During the spring, AI promoted sex change after 9weeks and the sperm produced was able to fertilize grouper oocytes. During the summer, the sex change was incomplete; intersex individuals were present and sperm was not released by any of the animals. Sex changed gonads had a lamellar architecture; cysts of spermatocytes and spermatozoa in the lumen of the germinal compartment. In the spring, after 4weeks, 11ketotestosterone (11KT) levels were higher in the AI than in control fish, and after 9weeks, coincident with semen release, testosterone levels increased in the AI group, while 11KT returned to the initial levels. Estradiol (E2) levels remained unchanged during the experimental period. Instead of decreasing throughout the period, as in control group, 17 α-OH progesterone levels did not change in the AI-treated fish, resulting in higher values after 9weeks when compared with control fish. fshβ and lhβ gene expression in the AI animals were lower compared with control fish after 9weeks. The use of AI was effective to obtain functional males during the breeding season. The increase in androgens, modulated by gonadotropins, triggered the sex change, enabling the development of male germ cells, whereas a decrease in E2 levels was not required to change sex in dusky grouper. © 2013 Elsevier Inc.
Keywords: Aromatase inhibitor; Artificial sex change; Follicle-stimulating hormone; Gonadal steroids; Letrozole; Luteinizing hormone